Ontario's Double Cohort - Winton, Sue; Jones, Glen (International Higher Education, 2004)
The “double cohort,” a perhaps unfamiliar concept outside Ontario, Canada, has been a source of angst for tens of thousands of students, their parents, and the province’s postsecondary institutions since 1997. This concept refers to the unique situation of two cohorts graduating from high school at the same time. The challenge of accommodating the double cohort in Ontario’s universities and colleges ultimately forced the government to fund a dramatic expansion of postsecondary education.